2020
DOI: 10.1016/j.celrep.2019.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Proteins Rtg1/3 Govern Sphingolipid Homeostasis in the Human-Associated Yeast Candida albicans

Abstract: Highlights d Rtg1/3 are key determinants of sphingolipid synthesis in the fungus Candida albicans d Rtg1/3 regulate enzymes involved in the synthesis of sphingolipids' building blocks d The stability of Rtg1/3 is dependent upon TOR and the ubiquitin ligase Ubr1 d The Rtg1/3 system is activated upon engulfment of C. albicans by human neutrophils

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 56 publications
5
47
1
Order By: Relevance
“…We first sought to visualize and quantify C. albicans transcripts encoding regulatory proteins, which typically are expressed at low abundance ( 25 , 26 ). We chose RTG3 and TYE7 which encode two transcription regulators that govern sphingolipid homeostasis and carbohydrate metabolism, respectively, and are key components of the regulatory network driving C. albicans commensalism and pathogenicity ( 27 29 ). To stringently evaluate whether the fluorescent signal corresponded to the transcripts of interest, we probed each mRNA in three corresponding strains, the wild type, deletion mutant, and a strain in which the gene of interest was under the control of the strong promoter TDH3 .…”
Section: Resultsmentioning
confidence: 99%
“…We first sought to visualize and quantify C. albicans transcripts encoding regulatory proteins, which typically are expressed at low abundance ( 25 , 26 ). We chose RTG3 and TYE7 which encode two transcription regulators that govern sphingolipid homeostasis and carbohydrate metabolism, respectively, and are key components of the regulatory network driving C. albicans commensalism and pathogenicity ( 27 29 ). To stringently evaluate whether the fluorescent signal corresponded to the transcripts of interest, we probed each mRNA in three corresponding strains, the wild type, deletion mutant, and a strain in which the gene of interest was under the control of the strong promoter TDH3 .…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that inhibition of the de novo synthesis of sphingolipids in C. albicans abrogated biofilm formation and could lead to abnormal hyphal growth (31,33,34). Not much is known about the transcriptional control of the sphingolipid homeostasis in Candida species, but transcription factors Rtg1/3 might be involved, at least in C. albicans (35).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained 41 to 48 million reads per sample (paired-end, 150-nt reads). Read processing, quality control, mapping, and differential gene expression analyses followed standard computational procedures described by our laboratory ( 59 , 67 ). Briefly, Illumina adaptor sequences were removed using the Trimmomatic tool (v.0.39) ( 68 ).…”
Section: Methodsmentioning
confidence: 99%